Philosophy's moods the affective grounds of thinking - SpringerLink (Online Service). (Dordrecht Springer Netherlands, 2011)
Philosophy's moods is a collection of original essays interrogating the inseparable bond between mood and philosophical thinking. What is the relationship between mood and thinking in philosophy? In what sense are we always already philosophizing from within a mood? What kinds of mood are central for shaping the space of philosophy? What is the philosophical imprint of Aristotle's wonder, Kant?s melancholy, Kierkegaard?s anxiety or Nietzsche's shamelessness Philosophy's Moods invites its readers to explore the above questions through diverse methodological perspectives. The collection includes fourteen contributions by internationally renowned scholars as well as younger and emerging voices. In pondering the place of the subjective and personal roots that thinking is typically called to overcome, the book challenges and articulates an alternative to a predominant tendency in philosophy to view the theoretical content and the affective side of thought as opposed to one another.
Electronic reproduction.
Keywords: Mood (Psychology).; Emotions (Philosophy).; Electronic books